Application of bacterial reverse mutation assay for detection of non-genotoxic carcinogens. (13th June 2017) - Kanode, Rewan; Chandra, Saurabh; Sharma, Sharad
Abstract: Non-genotoxic carcinogens may play a significant role in development of cancer. Currently short-term assays for mutagenicity classify genotoxic carcinogens and lack the abilities to detect epigenetic carcinogens. The need to develop an endpoint always remains to recognize potentially carcinogenic agents employing rapid and practical bioassays. For this, the present study utilized TA98 and TA1537 tester strains of Salmonella typhimurium to evaluate four non-genotoxic carcinogenic agents (Coumarin, β-Myrcene, Bis(2-ethylhexyl) phthalate and trans -anethole). These chemicals were tested individually and in combination with promutagens 2-aminoanthracene (2AA) and benzo(a)pyrene (BP) in presence of metabolic activation system (S9) by plate incorporation method. Exposure to all four test chemicals revealed marked increase of revertant colonies in promutagen combined groups as compared to promutagens alone. However significantly greater fold responses were observed with 2AA combination groups (Coumarin +2AA, β-Myrcene +2AA, Bis(2-ethylhexyl) phthalate +2AA and trans -anethole +2AA) with TA98 strain as compared with TA1537, which seems to have enhanced the mutagenic response of 2AA in metabolically activated conditions. It is concluded that out of both tester strains TA98 strain of Salmonella typhimurium has the potential to detect non-genotoxic carcinogens when combined with potent promutgens either by inhibiting or modulating activities of liver microsomal enzymes biochemically which may indirectly contribute to neoplastic alterations. Further this simple, short-term alternative assay may provide rapid information during extrapolative toxicology for differentiating genotoxic and non-genotoxic carcinogens.